Teachers' Efforts in Overcoming Reading Difficulties Among the First-Grade Students at MI Hijriyah II Palembang - Cherrysa Ariesty Wulandari; Aquami; Muhamad Afandi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study investigates the factors contributing to reading difficulties among first-grade students at MI Hijriyah II Palembang, the efforts made by teachers to overcome them, and the challenges faced. Using a descriptive qualitative approach through observation, interviews, and documentation, the study found that students’ reading difficulties are influenced by physiological, intellectual, environmental, socio-economic, and psychological factors. Teachers at MI Hijriyah II Palembang have implemented various effective strategies, including the use of picture/flash word cards, additional reading lessons, the provision of engaging books, game-based methods, group and individual guidance, a “classroom workshop,” word-by-word reading support, selection of books according to reading level, visual aids, creative ways of introducing letters, regular book reading sessions, parent collaboration, as well as motivation and rewards. However, teachers face challenges such as diverse student characteristics, lack of learning motivation, low comprehension levels, and limited time. This study highlights the need for a holistic approach to addressing reading difficulties, involving diverse interventions and close collaboration between teachers and parents.